SEKELUMIT MANGROVE DI SIRING MALAKA REKOMENDASI PENGELOLAAN BERKELANJUTAN - Yuliasamaya Yuliasamaya; Zulkarnaini Zulkarnaini; Syafriadiman Syafriadiman (Program Pascasarjana Universitas Riau, 2021)
A place in the corner of the Malacca Strait, precisely in Sungai Apit District, Siak Regency, the coastal area of Riau Province, has a role as the transportation routes that connect Bengkalis, Pekanbaru and Batam, as well as ships transit point in Malacca Strait. The area has a very small mangrove cover area but has many local communities who manage mangroves independently, in the midst of dense industrial operations in the area, especially with the Tanjung Buton area which is a development area of a national strategic project. The developments carried out in that place must be carried out in a sustainably, namely balanced in ecological, economic and socio-cultural aspects. Research in that place always discusses only one aspect of the three, moreover what is currently rife is ecotourism, so many researchers have explored the wealth of natural tourism and not a few have discussed its economic benefits. This study aims to analyse these three aspects to produce recommendations for sustainable mangrove management strategies. This research was conducted in 2019-2020 in a descriptive quantitative manner using the Rapid Appraisal method which collaborates the use of several modern technology instruments including remote sensing, transect mapping, and Monte Carlo analysis. The management strategy resulted from a layered analysis that is generally found in separate studies. The results of this study show that the level of sustainability of mangrove ecosystem management in Sungai Apit District is less sustainable. The ecological condition is classified as less sustainable, the economic condition is classified as quite sustainable, while the socio-cultural conditions are classified as unsustainable. The mangrove ecosystem management strategy from this research is the